Research and Development on a Nonviolent Communication Model Based on Contemplative Education in Schools under Pattani Primary Educational Service Area Office 1 - Kerdtip, Chawalit (Journal of Information and Learning [JIL], 2022)
This research and development investigated a nonviolent communication model based on contemplative education in school under Pattani Primary Educational Service Area Office 1. There were four phases in this research. In Phase 1, confirmatory factors for nonviolent communication were analyzed. The sample consisted of 616 directors and teachers under Pattani Primary Educational Service Area Office 1. Data in this research were gathered using Linkert-scale questionnaire as a tool. The total reliability value was .972. In Phase 2, a model was designed through two focus group discussions in which 10 experts and 20 participants from the sample group participated. The content analysis was employed. Phase 3 dealt with surveying perception of school directors, teachers, and students towards nonviolent communication skills. The survey was conducted with 85 samples in 2018 and 2019. Data in this research were gathered using Linkert-scale questionnaire as a tool. The total reliability value was .865. Mean value was employed. In Phase 4, the designated model was utillized at an implemented school in 2020. The questionnaire used in Phase 3 and a follow-up interview were employed, and the data were analyzed through mean value and content analysis. The findings revealed that 1) there were four factors for nonviolent communication with the values from 0.91 to 0.99, ranging from needs, observations, requests, and feelings respectively, that 2) nonviolent communication in contemplative education comprised three stages: awareness, change, and consistent skill improvement, that 3) overall self-perception on nonviolent communication had mean values at 3.27 in 2018 and at 4.23 in 2019, and that 4) the implementation of the model to the implemented school revealed significant self-perception on nonviolent communication with the mean value at 3.78. In content analysis, open communication, accepting difference, and positive and contented interactions have been improved in both schools.